Pengaruh Literasi Keuangan Locus Of Control, Gaya Hidup Hedonisme, Dan Efikasi Diri Keuangan Terhadap Perilaku Pengelolaan Keuangan - Monica, Massiva Virginia; Harahap, Aderina; Yuliana, -; Suheriyatmono, -; Luthfi, Muhammad (Universitas Malahayati, 2025)
This Study aims to determine the effect of financial literacy, locus of control, hedonistic lifestyle, and financial self efficacy on financial management behavior. This study uses a quantitative approach with datacollected through questionaires involving 100 respondents using purposive sampling, who are generation Z who transact usingShopeepay in Bandar Lampung. The analysis method used is multiple linier regression. The result show that Financial Literacy, Hedonistic Lifestyle, and Financial Self Efficacy have a significant partial effect on Financial manajemen Behavior, while the Locus of Control variable does not havea a significant effect on Financial Manajemen Behavior. Simultaneously, all variable have an effect on Financial Management Behavior.